A Brief Didactic Intervention to Improve Multiple-Choice Item-Writing Quality - Jonathan S Jones; Andrew W Phillips; Andrew M King; Molly K Estes; Lauren W Conlon; Kevin R Scott (eScholarship Publishing, University of California, 2018)
Audience: Emergency Medicine Residents, Faculty Introduction: High stakes examinations encountered throughout medical education are often composed of single best answer multiple-choice questions (MCQs). Many guidelines for writing MCQs exist, but often item writers receive little to no formal training. Flawed exam items have been shown to have lower discrimination values, potentially introducing construct-irrelevant variance to examinations, reducing their validity.1-3 Long-term faculty development in the area of item writing has been shown to improve examination item quality, with a pilot study showing that a more brief intervention had the same impact on quality of written items.4-6 Furthermore, when learners have been engaged in item writing, they have found the exercise to be a beneficial learning experience, with one study demonstrating an improved performance on a summative assessment as a result of participating in item writing.7-10 Objectives: The primary objective of this training module is to provide emergency medicine residents the basic knowledge necessary to write high quality structured single-best answer examination items through a brief, independent study format. Method: The training module is a PowerPoint-based lecture with recorded voiceover, which is provided in mp4 format.